The Polemic Of Discretion In Abuse Of Authority By Public Officials In The Perspective Of The Principles Of A Clean And Corruption-Free Legal State - Andik Puja Laksana; Suparno , Suparno (PT. ALHAFI BERKAH INDONESIA, 2025)
Discretion is a legal instrument given to public officials to make decisions or act under certain conditions without explicit laws and regulations. Discretion is critical in government, especially in providing flexibility for state apparatus to perform their duties and obligations. However, in practice, discretion is often misused by public officials under the pretext of broader administrative or policy interests. Abuse of authority through discretion can give rise to various legal problems, including increased practices of corruption, collusion, and nepotism (KKN), which are contrary to the principles of a clean and corruption-free legal state. Therefore, an in-depth study is needed regarding the limitations, supervision, and accountability mechanisms of public officials in implementing discretion so that it does not conflict with the principles of good governance and legal certainty. This study uses a normative juridical method with a statute and a conceptual approach. The analysis was conducted on various legal norms that regulate discretion, including the Law on Government Administration, as well as the principles of administrative law relating to the authority of public officials. In addition, this study also examines the mechanism of supervision of discretion to prevent abuse of authority that can harm the interests of society and the state. Thus, this study is expected to provide a deeper understanding of discretion in a state of law and provide recommendations on possible actions to strengthen the supervision and accountability of public officials in exercising their authority.